Організаційно-педагогічні умови формування соціально-правової компетентності курсантів ВВНЗ авіаційного профілю - Марченко, О. Г.; Marchenko, O. H.; Онипченко, П. М.; Onypchenko, P. M.; Ольга Марченко (Перспективи та інновації науки. - 2023. - № 15(33). - С. 326-338, 2023)
Визначено теоретичні і методичні засади запровадження організаційно-педагогічних умов формування соціально-правової компетенції курсантів ВВНЗ авіаційного профілю, яке сприятиме підвищенню якості професійної підготовки авіаційних військових фахівців. Наголошено, що організаційно-педагогічні умови організації навчального процесу, щодо формування соціально-правової компетентності курсанта ВВНЗ авіаційного профілю, можуть бути реалізовані через набуття ціннісних орієнтацій у професійній сфері, творчий потенціалу особистості, комунікативний аспект навчання, моральні орієнтири майбутнього офіцера, психофізіологічну готовність до професії військового льотчика, кваліфікаційного потенціалу процесу навчання.

The high-quality professional training of reliable military specialists at the Aviation Higher Education Institution requires the modernization of the organizational and pedagogical conditions of training in the context of a new educational paradigm, according to which the cadet becomes an equal participant in the educational process, its subject, who consciously chooses an individual learning trajectory that is free of breaks and bifurcations transforms into a path of professional growth. For this, it is necessary to study the state order for the training of aviation military specialists, to ensure the psychological and scientific-methodical readiness of the leadership, scientific-pedagogical workers, and cadets, to determine the organizational and pedagogical conditions for the introduction of a pedagogical system for the formation of the necessary competencies, the possibility of implementing the latest pedagogical technologies in this process. The formation of socio-legal competence, as a component of the militaryprofessional competence of aviation military specialists, touches on the social and legal aspects of the evolution of military professionalism, which takes place according to the scheme: a leader in battle – a manager – a technical specialist – a soldier – a politician. Socio-legal competence involves the development of the skills of productive cooperation, active interaction, persuasive and tolerant (legal) communication. The formation of these skills is impossible without the experience of socio-legal communication with other subjects of educational activity, the mastery of effective information technologies, which is possible in the presence of the property of self-organization and self-improvement of the communication system, which provides for direct and feedback communication between teachers and cadets. The activation of the socio-legal component of the military-professional competence of future aviation specialists in the conditions of aviation-related higher educational institutions involves the organization of opportunities for the transmission and assimilation of traditions, ideals, requirements for the future officer's model of behaviour in professional and everyday life, political and public activity. Therefore, the organizational and pedagogical conditions for the organization of the educational process, regarding the formation of the social and legal competence of the cadet of the aviation university of the aviation profile, can be realized through the acquisition of value orientations in the professional sphere, the creative potential of the individual, the communicative aspect of training, the moral orientations of the future officer, psychophysiological readiness for the profession of a military officer the pilot, the qualification potential of the training process.

Определены теоретические и методические основы внедрения организационно-педагогических условий формирования социально-правовой компетенции курсантов высшего военного учебного заведения авиационного профиля, которое будет способствовать повышению качества профессиональной подготовки авиационных военных специалистов.
Organizational and pedagogical conditions for the formation of social and legal competence of cadets Aviation profile High School
Keywords: вищий військовий навчальний заклад авіаційного профілю; higher military educational institution of the aviation profile; высшее военное учебное заведение авиационного профиля; авіаційний військовий фахівець; aviation military specialist; авиационный военный специалист; компетентність; competence; компетентность; курсант; cadet; навчальний процес; learning process; учебный процесс; організаційно-педагогічні умови; organizational and pedagogical conditions; организационно-педагогические условия; професійна підготовка; professional preparation; профессиональная подготовка; соціально-правова компетентність; socio-legal competence; социально-правовая компетентность